Assessment of scenarios for intensifying pasture management and grazing in fragile micro-watersheds of high Andean mountains - Jorge Eduardo Grijalva Olmedo; Paola Mercedes Palate Moreta; Roy Roger Vera-Vélez; Raúl Armando Ramos Veintimilla; Jean-François Tourrand; Arnulfo Portilla Narváez (Siembra)
In the Andean hillsides of Ecuador, indigenous populations use land mainly for grazing sheep and cattle. Animal response depends exclusively on the quality of forage and the soil’s physical and chemical conditions. The objective of this research was to evaluate two scenarios for intensifying pastures based on perennial ryegrass (Lolium perenne) and white clover (Trifolium repens), used at rest periods of 45- and 60 days in sites between 3,000-3,400 m a.s.l. used for grazing sheep and cows. These scenarios were compared with a natural grassland based on a plant community composed of Stipa ichu, Holcus lanatus, Rumex acetocella, and Paspalum sp., used in a traditional system with rest periods of 60-75 days in sites between 3,500-3,700 m a.s.l. in the Chimborazo River micro-watershed. Soil sampling was conducted at both sites to determine the soil fertility profile. Regarding the forage component, chemical composition, animal carrying capacity, milk production, and estimated enteric CH4 emissions were determined. In sheep serum, Ca, P, and Mg profiles, and the activity of AST, ALT, and FA enzymes were analyzed. The data were analyzed using ANOVA and Tukey 5% as a means comparison test. The results showed a better physicochemical property of the soil at the lower altitude. The intensification of pasture management and grazing through the utilization of rest periods of 45 days or less may represent a productive and low-emission option.